The Effect of Education and Training on Employee Productivity - Suwardhi Pantih (Golden Ratio of Data in Summary, 2024)
This study aims to investigate the effect of education and training on employee productivity. The research method used is descriptive-quantitative, with a focus on the causal relationship between education and training as the independent variables and productivity as the dependent variable. The results of the study show that training has a positive and significant effect on employee productivity, indicating the importance of investing in effective education and training programs to improve employee skills and knowledge and overall increase company productivity.